Easy Fix Concrete Block - Mohd Mustafa Al-Bakri, Abdullah (Malaysian Association of Research Scientists (MARS), 2010)
Mohd Mustafa Al-Bakri Abdullah and his team won silver at Malaysia Technology Expo (MTE) 2007, 29th - 31st Mac 2007 at Putra World Trade Centre (PWTC), Kuala Lumpur. MTE 2007 organized by MARS and PROTEMP Exhibition.